"Shades of Grey": Exploring Public Opinion about Later-Life Sexuality. Issue 4 (21st December 2020) - Gewirtz-Meydan, Ateret; Ayalon, Liat
ABSTRACT: Public opinion on later-life sexuality affects older people's sexual health, behaviour, and satisfaction. In this study, we explored public opinion on later-life sexuality by participants' responding to an open-ended question rather than rank their level of agreement or disagreement with different statements about older people's sexuality. Responses from 135 men and women reflecting on how sexuality changes in older age were thematically analysed. Five themes emerged, varying from positive to negative perceptions of later-life sexuality. Older people's sexuality was described as declining, non-existent, conservative, narrow, tedious, and boring, but also as encompassing more emotions and feelings; being better and more "complete". This study provides qualitative data and an opportunity to gain insights on valuable opinions on what young and middle-aged people think about later-life sexuality. Assessing what people think about later-life sexuality is the first stage in instilling more liberating views about the diversity of sexual expressions in old age.